Epidemiology of HIV and response to antiretroviral therapy in the middle aged and elderly. (December 2008) - Gebo, Kelly A
HIV is increasing in prevalence in the middle aged and older population owing to both increased longevity, and new infections in these populations. Highly active antiretrorival therapy (HAART) therapy may be less effective at restoring immune function in older patients compared with younger patients. There are significant toxicities associated with HAART therapy that, combined with decreased renal and liver function in older patients, may be more problematic in older HIV-infected patients. Comorbid disease is becoming an increasing problem with coadministration of multiple drugs and significant drug––drug interactions. Psychosocial issues in the older patient are often different than those in younger HIV-infected patients and providers should try to address these issues early. Finally, future research should work to identify the ideal timing and type of HAART regimens for older HIV-infected individuals.